PERTEK BRIDGE FROM THE OTTOMAN EMPIRE TO THE REPUBLIC - Cakar, Enver; Sen, Korkmaz; Kisa, Yavuz; Toprak, Ahmet; Olgun, Tuba Nur; Sahin, Murat (E.U. Printing and Publishing House, 2024)
Pertek, the district of Tunceli, is located in the Upper Euphrates Region of the Eastern Anatolia Region and in the Lower Murat Mountainous Region. It is surrounded by the Sakaltutan Mountains, an extension of the Eastern Taurus Mountains, from the northwest and the Murat River (now Keban Dam Lake) from the east to the west from the south. The Murat River, which flows from the Bing & ouml;l and Palu sides, reaches Keban in front of Pertek (Eski Pertek) by taking the Peri and Munzur streams, where it merges with the Karasu flowing from the Kemaliye side and takes the name Euphrates. Pertek is located on the historical road from Elaz & imath;& gbreve; (Harput) to Erzurum and Trabzon, that is to the Black Sea. This road was cut by the Murat River (today Keban Dam Lake), which was a natural obstacle between Harpout and Pertek. Since there was no bridge over the river, the crossings, which are made by ferries today, were made by rafts and keleks at first, and later by boats called ships. There is no information in the sources that a bridge was built over the Murat River in Pertek, which was home to many civilisations and located at a very strategic point, until the Republican Period. According to the Ottoman archive documents, a serious attempt was made to build a bridge here in 1886 and the project of the bridge was drawn after the exploration. This bridge was to be built between Harabe Han, located on Araba Street in Harput on the banks of the Murat River, and the town of Pertek on the opposite side of the water. This road and bridge would be used by everyone, and since the road from Pertek to Trabzon would pass through Dersim, it would also be a caravan route. For this purpose, it was also possible to repair the ruined inn on the Kharpert side. The Pertek Bridge was to be built on pontoon, for which mulberry wood, which was abundant in Palu and Pertek and was resistant to water, was to be used. These pontoons were to be connected to each other and then to the two ends of the bridge with thick and strong chains. The raw iron needed was to be supplied from Trabzon and Karahisar, as it could not be found in Kharpert. There were to be two arches in the centre of the bridge, wide enough for two carriages coming from opposite sides. In this case, the cost of the bridge was estimated to be 150 thousand kurus. After the bridge was built, the boats called ships would no longer be needed. For this reason, the state would lose 7 thousand piastres annually, and this loss would be compensated by the fees to be collected from those passing over the bridge. However, despite all these efforts, the construction of the bridge was not realised due to insufficient efforts and exploitation. The construction of a bridge over the Murat River in Pertek was only possible in the first years of the republic. This first bridge built of wood was rebuilt in 1929 when it collapsed due to the overflow of the river in 1939, a reinforced concrete bridge was built using the advanced technique of the time, and after serving the local people and passing passengers for a long time, it completed its historical function by remaining under the dam lake in 1974, with the construction of the Keban Dam and the start of water retention.
Keywords: Dersim; Pertek; Euphrates; Murat River; Historical Bridges